Net working capital strategy influencing beta coefficient based on companies listed on newconnect alternative exchange in Warsaw - Monika Bolek (e-Finanse: Financial Internet Quarterly, 2019)
The goal of this paper is to present the net working capital strategies relationship with the systematic risk ratio, namely beta coefficient, that is a measure of a stock's volatility in relation to the market. The strategy of financing assets reflected in net working capital is influencing the financial liquidity policy and the risk of the company thereafter. Decisions and strategies that are performed by management are assessed by investors when a company is listed on the exchange and should be reflected in share price volatility. The survey is based on quantitative analysis of NewConnect nonfinancial company data. The results of the analysis show that the relationship between net working capital indicators and beta coefficient is negative.
Keywords: G30; 330; net working capital; beta; risk